Multinational companies and transfer pricing manipulations in Nigeria: Challenges and way forward (Singaporean Journal of Business Economics and Management, 2024)
Transfer pricing manipulation has become a persistent dilemma in tax revenue collection worldwide and Nigeria in particular. It reduces the amount of revenue that the host nations generate. This study aims at examining the relationship between transfer pricing manipulation and economic growth in Nigeria. The study used secondary data from the Federal Bureau for Statistics and Central Bank of Nigeria Statistical Bulleting covering the period from year 2000 to 2024. The study used auto-regressive distributed lag (ARDL) technique for data analysis. The results show that the relationship between economic growth and explanatory factors such trade openness, government revenue, unemployment rate, and transfer pricing manipulation is negligible. Additionally, the outcome demonstrates a strong inverse relationship between economic growth and exchange rates. This study highlights a significant finding, which is that multinational corporations frequently abuse revenue to generate unjustified profits, adding needless expenses to the market, undermining the competitiveness of other businesses, and taking advantage of customers and purchasers. The study recommends that in order to verify the daily transaction operations of multinational corporations, the government should establish appropriate oversight of them. Federal Inland Revenue Service (FIRS) in collaboration with the Financial Reporting Council of Nigeria FRCN should modify the existing transfer pricing regulations to address the obstacles to its realistic execution while supporting the existing administrative and human skills of current policy operations in the country.